2021
DOI: 10.1038/s41524-021-00544-2
|View full text |Cite
|
Sign up to set email alerts
|

Radiative properties of quantum emitters in boron nitride from excited state calculations and Bayesian analysis

Abstract: Point defects in hexagonal boron nitride (hBN) have attracted growing attention as bright single-photon emitters. However, understanding of their atomic structure and radiative properties remains incomplete. Here we study the excited states and radiative lifetimes of over 20 native defects and carbon or oxygen impurities in hBN using ab initio density functional theory and GW plus Bethe-Salpeter equation calculations, generating a large data set of their emission energy, polarization and lifetime. We find a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 51 publications
(78 reference statements)
6
28
0
Order By: Relevance
“…Several bottomup growth techniques as well as post-processing approaches such as ion implantation or electron irradiation have been aimed at identifying the sources 12,13,[18][19][20] . In addition, multiple theoretical calculations show that different types of atomic defects may exist, including nitrogen or boron vacancy complexes, antisite defects, or substitutional defects with carbon or oxygen 14,15,17,[21][22][23][24] , but a conclusive evidence for these prediction results is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Several bottomup growth techniques as well as post-processing approaches such as ion implantation or electron irradiation have been aimed at identifying the sources 12,13,[18][19][20] . In addition, multiple theoretical calculations show that different types of atomic defects may exist, including nitrogen or boron vacancy complexes, antisite defects, or substitutional defects with carbon or oxygen 14,15,17,[21][22][23][24] , but a conclusive evidence for these prediction results is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…V B -derived defects are examples of defects that can be created intentionally, because of the prevalence of boron vacancies in hBN samples treated with electron bombardment . The photophysical characteristics of defects involving carbon are also relevant for advancing the objective of manipulating intentionally created defects, as several experimental groups have incorporated carbon into the hBN lattice. ,, Future works towards accurately determining the excited-state relaxation and reorganization energies for the promising defects are highly desirable, , since experimental works mostly report optical emission energies. However, it is known that the emission energies are slightly smaller than the absorption energies, by hundreds of meVs. ,,, The peak positions in the optical absorption spectra can also be directly compared with photoluminescence excitation spectra to guide the identification of the defect centers, as discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitatively accurate predictions of defect energy levels and optical spectra, as well as the relevant interband transition pairs, are a crucial first step to characterize and precisely manipulate the defect center-based SPEs in hBN. To our knowledge, there have only been a few GW-BSE calculations ,, on defects in hBN.…”
Section: Computational Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, group‐theoretical aspects are often used that rely on the symmetry of the considered defect structure. [ 85 ] Experiments have also shown that the level structure likely consists of at least one optically active excited state and one additional dark excited state energetically below the bright one, which is a possible third criterion of the emitter structure. Almost any considered defect structure should possess several dark states and therefore support this requirement.…”
Section: Theoretical Aspectsmentioning
confidence: 99%